(untitled) (Ustozlar uchun, 2026)
U.S. culture is a multifaceted culture in which different nationalities, races, and traditions are blended. It was formed primarily by immigrants from Europe, African slaves, and Native Americans. Later immigrants from Asia and Latin America also further enriched the cultural diversity. The ideas of individualism, freedom, and equality play an important role in U.S. culture. These values are closely related to the country’s history and political system. National holidays such as Thanksgiving and Independence Day have special significance in the culture. In the field of art and popular culture, the United States has had a huge impact on the world. Through Hollywood, the film industry, as well as music trends such as Jazz and Hip-hop, spread all over the world. The culture of the modern U.S. is constantly changing under the influence of technology, media, and globalization. At the same time, it continues to evolve while blending traditional values and new ideas.